Manganese toxicity suppressing nitrogen-fixing bacteria growth and impairing nitrogen uptake and utilization in sugarcane - Zhu, Hanyu; Pan, Junchen; Wei, Yanyan; Lan, Heyong; Yang, Shu; Li, Xiaofeng; Tang, Xinlian (Frontiers in Microbiology, 2025)
IntroductionSugarcane (Saccharum spp.) is a crucial crop for sugar and bioethanol production. However, sugarcane grown in the acidic soils of southern China often suffers from severe leaf chlorosis due to excessive soil manganese (Mn). This study investigates the effects of Mn toxicity on the physicochemical properties and microbial communities in sugarcane rhizosphere soil, as well as its impact on sugarcane growth and nitrogen uptake and utilization.MethodsSoil samples were collected from sugarcane fields with varying levels of Mn toxicity. Physicochemical properties of the rhizosphere soil were analyzed, including soil pH, available nitrogen, and microbial community composition. The impact of Mn toxicity on sugarcane growth was assessed through measurements of plant biomass, leaf chlorosis, and nitrogen uptake efficiency.ResultsMn toxicity significantly lowered soil pH and altered the soil microbial community structure. Bacterial genera such as Nocardioides and Sinomonas, which are involved in ureolysis, cellulolysis, and Mn oxidation, were promoted. In contrast, genera like Nitrospirota, associated with nitrogen fixation, were inhibited. This disruption hindered the conversion of soil ammonium nitrogen to nitrate nitrogen, reducing soil available nitrogen. Consequently, sugarcane growth and development were suppressed, and nitrogen uptake was limited.DiscussionThe findings highlight the detrimental effects of Mn toxicity on sugarcane cultivation in high-Mn areas. The altered microbial community composition and reduced soil nitrogen availability directly impact sugarcane growth. These results underscore the importance of applying appropriate fertilizers to mitigate Mn toxicity and improve soil fertility in such regions. Future research should focus on developing strategies to enhance soil nitrogen cycling and promote beneficial microbial communities to support sustainable sugarcane production.